2016
DOI: 10.1161/circresaha.116.309769
|View full text |Cite
|
Sign up to set email alerts
|

Hyperpolarized 13 C Metabolic MRI of the Human Heart

Abstract: Rationale:Altered cardiac energetics is known to play an important role in the progression toward heart failure. A noninvasive method for imaging metabolic markers that could be used in longitudinal studies would be useful for understanding therapeutic approaches that target metabolism.Objective:To demonstrate the first hyperpolarized 13C metabolic magnetic resonance imaging of the human heart.Methods and Results:Four healthy subjects underwent conventional proton cardiac magnetic resonance imaging followed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
317
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 316 publications
(326 citation statements)
references
References 21 publications
(23 reference statements)
8
317
0
1
Order By: Relevance
“…Its transformation into [1‐ 13 C]lactate, [1‐ 13 C]alanine or decarboxylation into 13 CO 2 can be observed within few seconds following to the injection of the HP metabolite in vivo or its administration to cells’ suspension. All these favorable features made HP [1‐ 13 C]pyruvate a quite promising molecular tool that allows to distinguish the metabolism of healthy and diseased tissues in cancer,, heart and brain…”
Section: Introductionmentioning
confidence: 99%
“…Its transformation into [1‐ 13 C]lactate, [1‐ 13 C]alanine or decarboxylation into 13 CO 2 can be observed within few seconds following to the injection of the HP metabolite in vivo or its administration to cells’ suspension. All these favorable features made HP [1‐ 13 C]pyruvate a quite promising molecular tool that allows to distinguish the metabolism of healthy and diseased tissues in cancer,, heart and brain…”
Section: Introductionmentioning
confidence: 99%
“…This enormous increase in sensitivity has enabled real‐time imaging of tissue metabolism in vivo following intravenous injection of hyperpolarized 13 C‐labelled substrates,36 including in humans 37, 38. Previous magnetic resonance spectroscopic imaging (MRSI) studies in rats injected with hyperpolarized [1‐ 13 C]pyruvate showed raised lactate‐to‐pyruvate ratios in CFA‐induced inflammation,39 which, considering the relationship observed between lactic acid and acidosis,9, 12, 13 suggested that acidosis must occur in this widely used model.…”
Section: Introductionmentioning
confidence: 99%
“…In solution, dihydrogen exchanges at ar ate k ex with the transientS ABRE complex IrH 2 S a S e [reaction (3)]. [26] We call this reactiont he "hydrogen exchange".…”
Section: Hydrogen Exchangementioning
confidence: 99%
“…The hyperpolarization (HP) of nuclear spins promises to revolutionize medical diagnostics [1][2][3][4][5][6][7][8][9][10] and chemical analysis [11][12][13][14][15] alike. Amongo thers, signal amplification by reversible exchange (SABRE), discovered in 2008, [16] is an up-and-coming technique with unique properties,i ncluding continuous hyperpolarization.…”
Section: Introductionmentioning
confidence: 99%